THE IMPLEMENTATION OF THE BABY FRIENDLY HOSPITAL INITIATIVE ON HEALTH CARE FACILITIES PROMOTES TO INCREASE OF BREASTFEEDING LEVEL - Kozakevich, V.K.; Kozakevich, O.B.; Ovdienko, O.D.; Kabika, T.V.; Mednik, N.V.; Pavlenko, V.A. (World of Medicine and Biology, 2012)
The implementation of the Baby Friendly Hospital Initiative on health care facilities promotes to increase of breastfeeding level.
Keywords: breastfeeding; lactation; initiative; duration